PRINCIPAL'S LEADERSHIP STRATEGY IN REALIZING INDEPENDENT LEARNING AT FITRAH AL-FIKRI ISLAMIC ELEMENTARY SCHOOL - Adawiyah, Rabiatul; Kurniawan; Abdurrohman, Asep; Muthmainnah, Nur Shafiyyah (TADBIRUNA: Jurnal Manajemen Pendidikan Islam, 2026)
This study explores the leadership strategies employed by a principal in implementing the Merdeka Belajar (Independent Learning) curriculum at SD Islam Fitrah Al-Fikri, an Islamic elementary school in Depok, Indonesia. Data were collected using a qualitative case study approach through in-depth interviews with the principal and five teachers, as well as observations and document analysis. Findings indicate that the principal plays a pivotal role in shaping the school's vision, empowering teachers, fostering an innovative school culture, and integrating Islamic values into curriculum implementation. Leadership strategies include participatory vision development, reflective supervision, collaborative decision-making, and continuous professional development. These strategies align with the principles of school-based management and contribute to the holistic and contextual implementation of Independent Learning. The study offers a practical model for Islamic schools seeking to align national education reform with religious and local values